2016
DOI: 10.1002/ejoc.201501479
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Syntheses of (R)‐ and (S)‐Naphthotectone, and Stereochemical Assignment of the Natural Product

Abstract: Both isomers of naphthotectone, an isoprenoid quinone from Verbenaceae Tectona grandis possessing interesting biological activities, were enantioselectively obtained by two different synthetic routes in which the carbon side-chain of the naphthoquinone core was introduced using either a Sonogashira or a Heck coupling reaction. In both cases, the naphthoquinone core of the final products was obtained by a late-stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The ESI-Q-Orbitrap MS { m / z 301.08969 [M + H] + (calcd for C 17 H 17 O 3 S, 301.08929)} and 1 H-, 13 C- ( Table 4 , CD 3 OD), 2D- ( 1 H- 1 H COSY, HSQC, HMBC) NMR experiments suggested that there was one more acetyl group [δ H 2.07 (3H, s, H 3 -2′′′), δ C 172.3 (C-1′′′)] at C-4′′ of aglycone than 3 . Finally, comparing the optical rotation { − 8.9° (MeOH)} with reference [ 36 ], the absolute configuration of 4 was revealed to be 3′′ S . Thus, its structure was determined as 3′′-ethoxy-(3′′ S )-pluthiophenol-4′′-acetate.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The ESI-Q-Orbitrap MS { m / z 301.08969 [M + H] + (calcd for C 17 H 17 O 3 S, 301.08929)} and 1 H-, 13 C- ( Table 4 , CD 3 OD), 2D- ( 1 H- 1 H COSY, HSQC, HMBC) NMR experiments suggested that there was one more acetyl group [δ H 2.07 (3H, s, H 3 -2′′′), δ C 172.3 (C-1′′′)] at C-4′′ of aglycone than 3 . Finally, comparing the optical rotation { − 8.9° (MeOH)} with reference [ 36 ], the absolute configuration of 4 was revealed to be 3′′ S . Thus, its structure was determined as 3′′-ethoxy-(3′′ S )-pluthiophenol-4′′-acetate.…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, the planar structure of 1 was determined. Finally, through the comparison of the optical rotation { + 11.4° (MeOH)} of 1 with those of ( R )- and ( S )-(3 E )-2-hydroxy-2-methyl-4-[1,8:4,5-bis(methylenedioxy)-2-naphthyl]but-3-enyl acetate, { R : + 22.6° (MeOH); S : − 20.0° (MeOH)], respectively} [ 36 ], its absolute configuration was elucidated to be 3′′ R .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations